Pemetaan Pola Terjadinya Gempa Bumi Di Indonesia Dengan Metode Fraktal - Doddy Restuning Galih; Lina hadayani (Indonesian Institute of Sciences, 2007)
Earthquake pattern mapping in Indonesia was done. This mapping conducted for the use of earthquake hazard area zonation, considering Indonesia located in very active tectonic area. Although in general Indonesia is a region with high risk earthquake disaster, the risk at each region is different one from the other. This mapping are done by grouping and differentiating each region in the region by the level of its earthquake hazard risk using fractal analysis. Seismic activities analysis using this theory show that the region of Maluku, Banda and its surroundings are place at the highest for earthquake risk disaster and Kalimantan place at the lowest part.